INTERACTIVE LECTURE: THE ROLE OF VIDEOS AND GAMES IN FOSTER STUDENTS’ TEAMWORK SKILLS (International Journal of Innovative Technologies in Economy, 2024)
Teamwork is a vehicle to help an organization achieve a competitive advantage. How to create the foundation of teamwork is becoming important for every organization worldwide. Therefore, the concept of teamwork is learned at every level of organization, including enterprises and schools. Because this concept is important, how to learn teamwork is developed by academics. Then we introduce a method to learn teamwork, i.e., an interactive lecture approach. This method gives a fun way to deliver the concept of teamwork to students. The purpose of this study is to analyze the implementation of an interactive lecture approach to help students acquire the concepts of teamwork. The study employs an experimental method with a pre-and post-test design without random assignment. The participants are forty-two students enrolling in a bachelor program at a private institute of technology in Cambodia. This study suggests that interactive lectures combining lectures, videos, and games have the potential to be an effective method to convey the concepts of teamwork. This finding supports learner-centered and multimodal learning theories and the importance of using various modes and media in a learning process.